(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة على خمسة مواقع في مياه المنطقة الشاطئية لمدينة اللاذقية وهي منطقة برج القصب , ابن هاني ، المعهد العالي للبحوث البحرية , المريديان , الشقيفات الواقعة قرب جبلة . تم خلالها جمع 165 عينة من عمق 0- 5 م، اعتباراً من شهر حزيران 2006حتى شهر تشرين الثاني 2007 . تم تمييز أربعة أنواع تابعة لجنسين هما Cymadusa و Amphithoe وبدورهما يتبعان إلى فصيلة Amphithoidae موضوع البحث ( وجميع هذه المراتب التصنيفية تسجل لأول مرة في سورية ), والأنواع المسجلة هي : C . filosa , A. ramondi , A. riedli , A. ferox . This study was conducted on 5 locations in the coastal region of Lattakia: Borj alkasab, Ras Ibn Hani, Marine Research Institute, Meridian, and Shkayfat. From June 2006 to Nov. 2007,165 samples were collected at 0-5 m deep. Four species were classified as belonging to two genres: Amphithoe and Cymadusa, which in turn belong to the Amphithoidae Family (All these classificatory categories have been recorded for the first time in Syria).These species are: C. filosa, A. ramondi, A. riedli, and A. ferox.